Preparation and photocatalytic activity of MAO-TiO2 films formed on titanium doped with V2O5 and Ag2O. (2nd January 2016) - Xiang, N.; Song, R. G.; Xiang, B.; Xiong, Y.; Li, H.; Wang, Z. X.
Abstract : First, microarc oxidation (MAO)-TiO2 films were prepared on titanium in a phosphate electrolyte to study the optimum treatment time for photocatalysis, and then, the doping process was carried out under the condition above. The phase composition and morphology of the films with two doping agents were characterised by X-ray diffraction (XRD) and scanning electron microscopy. The photocatalytic activity of the films was evaluated by photocatalytic decolorisation of methylene blue (MB) in aqueous solution. The results showed that the Ag2 O–TiO2 composite film is composed of anatase and rutile, while the V2 O5 –TiO2 composite film is only composed of anatase. The photocatalytic tests proved that the composite films were of the ability to enhance the photocatalytic activity of MAO-TiO2 film, but exhibited different photocatalytic efficiency. In addition, V2 O5 was more suitable for doping to some extent on photocatalytic activity for MAO-TiO2 film than Ag2 O.